The Effectiveness Of Teaching Grammar In Writing Context As Communicative Approach To The Fourth Semester of English Department Of STKIP PGRI Jombang. - Hartia Novianti (STKIP PGRI Jombang, 2015)
Grammar is one of the most difficult issues of language teaching. Grammar in writing context holds an important place to motivate learners if grammar is taught in communicative approach as students will have an opportunity to perceive how the new grammar structures work. It includes knowledge of how to use language which some psycholinguist (Anderson 2005) have called procedural knowledge or implicit knowledge as opposed to declarative knowledge or explicit knowledge. In fact, many applied linguists believe that the learners’ ability to communicate can be developed alongside their evolving knowledge about grammar. Through lot of opportunities to explore grammar in context, the learners have the chance to see how and why different forms can be used to express different communicative meanings Grammar in writing context as communicative apptoach also could encourage students to use the forms in expressing their own content and to help students see the usefulness of what they have learned (Weaver:1996). The result of the study showed that the mean score in the posttest was higher than in the pretest; and the mean score increased 18.5 point after treatment. Meanwhile the mean score from the control group were respectively 59.75 and 64.5 in the posttest, meaning that the mean score increased only 4.75 point after treatment . Briefly of the experimental group were higher than control one Therefore it could be concluded that students taught grammar in writing context as communicative approach gain better achievement than those taught in pattern practice drills.